DYEING OF SILK AND WOOLEN FABRIC WITH DYE OBTAINED FROM INDIGOFERA TINCTORIA PLANT AND DETERMINATION OF COLOR FASTNESS (World Bulletin of Social Sciences, 2023)
In this study, the object of the study were fibers consisting of 100% wool and silk fibers, the degree of whiteness of the wool fiber was 36.6%, the silk fiber was 40.8%. For staining, natural indigo dye was used, obtained by extracting the plant Indigofera tinctoria L., and Al2(SO4)3 was used as a mordant. Dyeing of protein fibers was carried out in the following technological sequence: samples of woolen and silk fibers that underwent the process of preparation for finishing were treated in a 3-10% indigo solution containing 2.5 g/l Al2(SO4)3 at a temperature of 90-950C for 60 minutes. Then 3% acetic acid was added to the solution and the process was continued at this temperature for 10 minutes. The color characteristics of indigo-dyed protein fibers were determined on a laboratory colorimeter under standard D65 irradiation. To systematize color characteristics, a system of color circles is used and the L.a.b. color model was used. Geographic coordinates - L*, a* and b* Color values such as latitude, longitude and altitude provide information about where the color is located and about it. The L* coordinate indicates the brightness of the color, C* - color saturation, h - chromaticity, a* - the presence of red or green, b* - the presence of yellow and blue. The color qualities of all samples were determined at a wavelength of 360 nm. Experiments have shown that in the process of dyeing natural fibers with natural indigo dye, a certain type of mordant is used to create a lasting color, and by changing the concentration of the dye in the dye solution, blue colors of different colors can be obtained using one dye.
Keywords: wool fiber; silk fiber; protein fiber; color